The Balkans as "Double Transit Space": Boundary Demarcations and Boundary Transgressions Between Local Inhabitants and "Transit Migrants" in the Shadow of the EU Border Regime. Issue 2 (4th March 2023) - Leutloff-Grandits, Carolin
ABSTRACT: To introduce the special section, this article presents an analysis of the dynamics of border closures and openings in the countries of the "Western Balkans." It examines the interconnections between the situation of so-called "transit migrants" on their way through these countries to the EU and the particular position of these countries in the protracted EU accession process, which also affects the situation of the local population. Highlighting the dual nature of – often simultaneous – border closures and border openings, the article first describes the changing mobility options for residents of various Balkan countries in the context of uneven EU accession processes, before outlining the relationship between EU migration management in the "Western Balkans" and the movements of "transit migrants" through and within the Balkans. The aim of the article is to raise awareness of the interconnectedness of the two perspectives on mobility and the different border and demarcation processes unfolding within the EU border and migration regime, which have spatial as well as temporal and social dimensions. These processes lead to various distinctions, but also to connections between migrants from the Global South and the local population in the various Balkan countries, which are further elaborated in the contributions to this special section.